2006
DOI: 10.1111/j.1748-0361.2006.00060.x
|View full text |Cite
|
Sign up to set email alerts
|

Preventive Care in Appalachia: Use of the Theory of Planned Behavior to Identify Barriers to Participation in Cholesterol Screenings Among West Virginians

Abstract: Attitudinal, social normative, and environmental barriers to health screenings may be characteristic of impoverished rural Appalachians. Interventions are being designed to target these belief barriers to improve participation in cholesterol screenings for fifth graders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 28 publications
2
47
0
Order By: Relevance
“…However, examinations of demographics among our larger sample (all CARDIAC children not just those with AN) revealed only two statistically signifi cant differences; i.e., parents of participating children are more likely to have health insurance and participating children are more likely to have regular health care providers. [44] This suggests that our active consent process might be under representing rather than over representing the health problems of WV children.…”
Section: Original Articlementioning
confidence: 98%
“…However, examinations of demographics among our larger sample (all CARDIAC children not just those with AN) revealed only two statistically signifi cant differences; i.e., parents of participating children are more likely to have health insurance and participating children are more likely to have regular health care providers. [44] This suggests that our active consent process might be under representing rather than over representing the health problems of WV children.…”
Section: Original Articlementioning
confidence: 98%
“…Or stated otherwise: having a positive intention not automatically leads to participation: what people say is not always what they do. In this study the TPB, which already has been used successfully in cervical cancer and cholesterol-screening studies, 33,34 was found to offer a useful framework for exploring the determinants of participation in preconceptional CF and/or HbPs carrier couple screening. The TPB determinants (attitude, social norm, and perceived behavioural control) explained a considerable amount of the total variance in the intention to participate in the current carrier testing (29%), and in a futurescreening programme (36%).…”
Section: Determinants Of Intention and Participationmentioning
confidence: 99%
“…Three studies described different components of a large school-based screening intervention (the CARDIAC project) 20,22,24 ; the rest represented separate studies.…”
Section: Description Of Studiesmentioning
confidence: 99%
“…Twenty-one, including nine new studies published since 2005 [19][20][21][22][23][24][25][26][27] , were eligible for inclusion as shown in Figure 2. Three studies described different components of a large school-based screening intervention (the CARDIAC project) 20,22,24 ; the rest represented separate studies.…”
Section: Description Of Studiesmentioning
confidence: 99%